ALIEN FLORA OF SUMATRA I: TEN NEW RECORDS - W.A. Mustaqim; Andri Y. Persada; Herlina P.E. Sari; Kartika A. Putri; Muhammad R. Hariri (PTTI, 2022)
The diversity of plants in Sumatra can be considered poorly known for the native species and the alien or non-native species. Recently, some new records of alien plant species have been added to the flora of Sumatra. Explorations were conducted to look for another undocumented alien plant species in this island in Langsa City, Aceh Province and Ogan Komering Ulu Regency, Sumatra Selatan Province. The results showed ten additional records of alien plants for Sumatra: Acalypha herzogiana (Euphorbiaceae), Coccinia grandis (Cucurbitaceae), Coleus monostachyus (Lamiaceae), Crossandra infundibuliformis (Acanthaceae), Ficus natalensis subsp. leprieurii (Moraceae), Melaleuca linariifolia (Myrtaceae), Ochna thomasiana (Ochnaceae), Ruellia simplex (Acanthaceae), Solanum diphyllum (Solanaceae), and Wrightia antidysenterica (Apocynaceae). Two of them (C. monostachyus and S. diphyllum) are already naturalized while others are in cultivation, or a few of them relicts of it. All species are listed, discussed, and provided with photographs to aid identification.